RELEGIUSITAS DALAM USFŪR MIN AL-SYARQ KARYA TAUFĪQ AL-HAKĪM - Yulia Nasrul Latifi (Sunan Kalijaga State Islamic University Yogyakarta, 2010)
The aim of this writing is to discover the varieties of forms of religious experience from Usfu> r min al-Syarq, a novel written by Taufiq al-Haki> m. By focusing on the ‘religiosity’ in the literary study, which is based on the protagonist's attitude as well as their thinking and the plot of story, this study has come up with several conclusions on the forms of religious experience, which are: 1) total experience from the presence of God, 2) strength and firmness on getting the calamity or disaster, 3) total experience of the mighty God and the unity of human being, 4) total experience from the beauty of death, and 5) peacefulness based on the true faith.